Paradigma Interpretif dan Pendekatan Kualitatif Dalam Pendidikan Matematika - Manullang, Mindo; Elia Elfani; Izwita Dewi; Edy Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Contemporary approaches to mathematics education play a vital role not only in assessing learning outcomes but also in uncovering the subjective meanings embedded in students’ learning processes. The interpretive paradigm provides a conceptual framework that emphasizes understanding social constructions, personal meanings, and the unique experiences of learners. This paradigm underpins qualitative research in education, particularly when the focus is on in-depth exploration of how students interpret and internalize mathematical concepts. This article aims to review recent literature that applies the interpretive paradigm within the field of mathematics education. Findings indicate that this approach is effective in revealing students’ perceptions of mathematics, their learning strategies, and the emotional and social challenges they encounter throughout the learning process. A literature review of publications from the past five years reveals that the interpretive paradigm enables researchers to gain deeper insights into students’ cognitive and affective domains areas often overlooked by quantitative methods. Predominant methodologies such as in-depth interviews, participatory observation, narrative reflection, and case studies facilitate a holistic and contextualized understanding of learning experiences. Furthermore, this paradigm repositions teachers not merely as transmitters of content, but as facilitators who are attuned to the social, cultural, and psychological backgrounds of their students. The findings from this review offer significant implications for the development of inclusive curricula, reflective and personalized instructional strategies, and more humane, context-sensitive assessment models. In this regard, the interpretive paradigm contributes to shaping a mathematics education system that is more empathetic, relevant, and meaningful for students from diverse backgrounds and with varied learning needs in the modern educational landscape.